Iron overload and its impact on outcome of patients with hematological diseases. (October 2020) - Franke, Georg-Nikolaus; Kubasch, Anne Sophie; Cross, Michael; Vucinic, Vladan; Platzbecker, Uwe
Abstract: Systemic iron overload (SIO) is a common challenge in patients with hematological diseases and develops as a result of ineffective erythropoiesis, multiple red blood cell (RBC) transfusions and disease-specific therapies. Iron homeostasis is tightly regulated as there is no physiological pathway to excrete iron from the body. Excess iron is, therefore, stored in tissues like liver, heart and bone marrow and can lead to progressive organ damage. The presence of free iron in the form of non-transferrin bound iron (NTBI) is especially detrimental. Reactive oxygen species can also cause stromal damage in the bone marrow and promote leukemic cell growth in vitro. In acute leukemias and myelodysplastic syndromes outcome is worse in patients with SIO compared to patients without. Especially in patients undergoing allogeneic HSCT presence of NTBI before or during transplant has been shown to negatively affect non-relapse mortality and overall survival. Although the mechanisms, of how these effects are mediated by SIO are not very well understood monitoring of iron status by serum markers and imaging techniques is, therefore, mandatory especially in these patients. Whether peri-interventional iron chelation may improve outcome of these patients is part of current clinical research.